Table of Content - - (Journal of Arabic Language Sciences and Literature, 2023)
Table of Content:1. Hajib bin Zarara Al-Tamimi and his intellectual contributions before IslamMr. Barka Abdoulaye Abdelhadi , Prof. Ousmane Mahamat Adam , Dr. Mouhamadou Chouibou2. Ibn Malik's Approach in Presenting Syntactic and Morphological Judgements; A study in AlfiyahMrs. Shahd Sabir Toukhi, Dr. Hanan Ahmed Al-Rajhi3. The importance of justifications and their impact on building the grammatical ruleDr. Siham Youisf Keadan4. Referencing Words in Surah Al-Nabba: Linguistic Study in Light of Text LinguisticsAsst-Prof. Omraan Mohamad Abdulrazak, Co-Prof. Mahmmud Hussein Al-Azazmeh5. Description of Development in Andalusian Poetry "The Palaces of the Kings of the Taifas" Artistic StudyMr. Mutair Eid M. Alatawi6. The Image of Horse in Antara PoetryMr. Khadir Ali Bsharat7. The birth of Arabic Grammar and Its OriginsDr. Sounia Mohammad Altwassi
Keywords: Journal of Arabic Language and Literature